Abnormal growth of 100 grains and strong Cube texture in strip cast Fe-Si electrical steel. (1st April 2018) - Fang, F.; Zhang, Y.X.; Lu, X.; Wang, Y.; Lan, M.F.; Yuan, G.; Misra, R.D.K.; Wang, G.D.
Abstract: High-grade non-oriented electrical steel was successfully processed by controlling texture using strip casting technology. Remarkable abnormal grain growth of 100 grains occurred in the as-cast strip after isothermal annealing. This phenomenon is considered to be the synergistic effect involving the size advantage of coarse columnar grains and surface energy, where the normal grain growth was inhibited by thermal grooving in the surface layer. Special rotation path was identified during the cold rolling process and metastable 118 〈110〉–113 〈110〉 texture dominated the deformation texture. The final annealed sheet exhibited strong Cube texture together with significantly superior magnetic properties. Graphical abstract: Image 1